HUBUNGAN KEMANDIRIAN ANAK USIA DINI TERHADAP KEMAMPUAN INTELEKTUAL - Santi Santi; Komala Komala (IKIP Siliwangi, 2021)
Independence is the process of children's growth and development and habituation of daily activities, in solving their own problems so that intellectual abilities grow, based on the observations of researchers at Sukrilah PAUD, it was found that some children were not independent and had no responsibility to the teacher's orders, making it difficult for their intellectual development. This is because children should be accustomed to carrying out activities related to the needs or needs of children independently from childhood, the researchers tried to examine the relationship, independence of early childhood to their intellectual abilities. The population in this study were all children of PAUD Sukrilah, Cianjur, while the research sample was 10 children of grade B. The approach used in this research process was quantitative with a correlational method. Data collection techniques, based on observations of children in the learning process, continued with correlational data analysis using SPSS.22 software. Based on the results of correlational research, it was obtained that sig 0.001 <0.005 means that H0 is rejected, so there is a clear influence of children's independence on intellectual abilities, this is indicated by independent children who are able to obey orders ordered by the teacher responsibly.Kemandirian adalah proses tumbuh kembang anak dan pembiasaan kegiatan sehari-hari, dalam menyelesaikan permasalahnya sendiri sehingga tumbuh kemampuan intelektual, berdasarkan pengamatan peneliti di PAUD Sukrilah ditemukan beberapa anak yang belum mandiri dan belum tanggungjawab terhadap perintah guru, sehingga sulit bagi perkembangan intelektualnya. Hal tersebut sebab anak seharusnya di biasakan untuk melakukan kegiatan yang berkenaan dengan keperluan atau kebutuhan anak secara mandiri dari sejak kecil maka peneliti mencoba meneliti hubungan, kemandirian anak usia dini terhadap kemampuan intelektualnya. Populasi dalam penelitian ini adalah seluruh anak PAUD Sukrilah, Cianjur, sedangkan sampel penelitiannya adalah 10 anak kelas B. Pendekatan yang dipakai dalam proses penelitian ini adalah kuantitatif dengan metodenya yaitu korelasional. Teknik pengumpulan data, berdasarkan observasi terhadap anak dalam proses pembelajaran, dilanjutkan dengan analisis data korelasional menggunakan sofware SPSS.22. Berdasarkan hasil penelitian korelasional maka diperoleh sig 0,001<0,005 artinya tolak H0 maka, terdapat pengaruh yang jelas dari kemandirian anak terhadap kemampuan intelektual, hal ini ditandai oleh anak yang mandiri mampu mematuhi perintah yang diperintahkan guru secara tanggung jawab.